Pengetahuan Inisiasi Menyusu Dini Berdasarkan Karakteristik Ibu Hamil di Puskesmas Palmerah - Reni Nofita; Nuntarsih Nuntarsih; Dorsinta Siallagan (Indonesian Journal of Midwifery (IJM), 2020)
The policy of early initiation of breastfeeding has been socialized in Indonesia since August 2007 (Roesli, 2008). The World Health Organization (WHO) has recommended that all babies get colostrum, namely breast milk on the first and second days to fight various infections and get exclusive breastfeeding for 6 months (Ministry of Health 2012). The IMD implementation policy is also expected to reduce infant mortality (IMD). In infant mortality, 40% occurs in the first month of life and early initiation of breastfeeding can reduce these risk factors for death, thereby reducing 22% for 28-day infant mortality. The research design was a cross sectional study using primary data (questionnaire). This sample uses accidental sampling method. The results showed that of the 87 respondents at Puskesmas Palmerah, the age of 20-35 years old mothers who had good knowledge about IMD were 30 respondents (34.5%), respondents with high education (SMA-PT) had good knowledge about IMD as many as 51 respondents ( 58.62%), respondents who work and have good knowledge about IMD are 24 respondents (27.59%), respondents who are experienced and have good knowledge about IMD are 42 respondents (48.28%), respondents who receive information and have Good knowledge about IMD was 69 (79.31%), while the related variables included age, education and experience with a P value of 0.384 greater than Î±, namely 0.05. Conclusion. Characteristics of age, education level, experience are closely related to the knowledge possessed by pregnant women, especially those related to knowledge of IMD. Meanwhile, the factor that is not related to the success of IMD is the source of information. Suggestion. There needs to be an effort to do outreach activities on Early Initiation of Breastfeeding (IMD) or supporting facilities to increase the knowledge of pregnant women, especially in the third timester.Keywords: Knowledge, IMD, Characteristics